2012
DOI: 10.2343/geochemj.2.0211
|View full text |Cite
|
Sign up to set email alerts
|

Temporal variation of 134Cs and 137Cs activities in surface water at stations along the coastline near the Fukushima Dai-ichi Nuclear Power Plant accident site, Japan

Abstract: heavily damaged and caused radionuclides to be discharged into the atmosphere and ocean (Chino et al., 2011; Tsumune et al., 2011). In this paper, we focus on the trend of 134 Cs and 137 Cs radioactivities at Hasaki, a coastal station on the east coast of Honshu, and other coastal stations, including the FNPP1 site. Because these stations are located in the densely populated Tohoku and Kanto areas of Honshu, the behaviour of 134 Cs and 137 Cs (radiocaesium) in coastal waters is important for understanding the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
73
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 101 publications
(83 citation statements)
references
References 11 publications
9
73
1
Order By: Relevance
“…In July and August, the plume was predominantly transported towards the north and gradually dispersed into the interior of the Pacific Ocean. These results are consistent with the 137 Cs samples collected at Hasaki (a coastal station 180 km south of FNPP) by Aoyama et al (2012) as well as measurements made at ten sites along the northern coast of Sanriku and Tsugaru Strait north of FNPP by Inoue et al (2012).…”
Section: Comparisons Between High-and Coarse-resolution Modelssupporting
confidence: 79%
“…In July and August, the plume was predominantly transported towards the north and gradually dispersed into the interior of the Pacific Ocean. These results are consistent with the 137 Cs samples collected at Hasaki (a coastal station 180 km south of FNPP) by Aoyama et al (2012) as well as measurements made at ten sites along the northern coast of Sanriku and Tsugaru Strait north of FNPP by Inoue et al (2012).…”
Section: Comparisons Between High-and Coarse-resolution Modelssupporting
confidence: 79%
“…The low concentration of radioactive Cs in the southern KE was also confi rmed by fi eld observations of seawater (Buesseler et al 2011(Buesseler et al , 2012Aoyama et al 2012 ) and simulation models . Thus, the majority of radioactive Cs directly released to the ocean from the FNPP was not dispersed south of the KE near the east coast of Japan in 2011; rather, the detection of 134 Cs at three stations along with the 175°30′E transect and station located south of the KE (35°N-144°E) in July 2011 and stations around 30°N in October 2011 may indicate the effect of atmospheric deposition.…”
Section: Eastward Dispersion In Surface Seawatermentioning
confidence: 99%
“…Figure 2.12 shows temporal variations of 137 Cs off the coast of East Japan based on selected data sets Buesseler et al 2011 ;Kaeriyama et al 2014b , d ;Kaeriyama, unpublished data). To compare the decreasing trend of FNPPderived radioactive Cs within these data sets, the data of Aoyama et al ( 2012 ) and Buesseler et al ( 2011 ) were plotted from the timing of the observed peak concentration. Exponential decrease was observed in each data set.…”
Section: Cs and 137 Cs Around Japan Islandsmentioning
confidence: 99%
“…The distribution of 134 Cs in the surface sediments should mimic that of 137 Cs because the initial 134 Cs/ 137 Cs ratio at the time of the accident was 1 (e.g., Aoyama et al 2012;Buesseler et al 2012 …”
Section: Distributions Of 134 Cs Concentrations In Surface Sedimentmentioning
confidence: 99%